2015
DOI: 10.1007/s00702-015-1448-7
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia complaints and substance use in German adolescents: did we underestimate the role of coffee consumption? Results of the KiGGS study

Abstract: The purpose of the study was to study the associations of tobacco, alcohol, marijuana, and coffee use and insomnia complaints (IC) in adolescents with special consideration of the influence of coffee consumption on these relationships. 7698 Subjects aged 11-17 years were investigated in a cross-sectional study within the German Health Interview and Examination Survey for Children and Adolescents. Self-report questionnaires were distributed to the participants. Hierarchical regression analyses were performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Previous studies have suggested that gender, levels of education or socioeconomic status, marital status, smoking and alcohol consumption, caffeine intake, and psychiatric comorbidities, such as depression and anxiety, are associated with insomnia. More specifically, these past studies indicate that being female, having a lower level of education and socioeconomic status, greater alcohol consumption and caffeine intake, and simultaneously suffering from other psychological disorders are strongly associated with insomnia [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that gender, levels of education or socioeconomic status, marital status, smoking and alcohol consumption, caffeine intake, and psychiatric comorbidities, such as depression and anxiety, are associated with insomnia. More specifically, these past studies indicate that being female, having a lower level of education and socioeconomic status, greater alcohol consumption and caffeine intake, and simultaneously suffering from other psychological disorders are strongly associated with insomnia [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other compounds present in coffee are also found to have anti-inflammatory and anti-carcinogenic effects such as the induction of enzymes responsible for carcinogen detoxification, inhibition of carcinogen activation activities and stimulation of intracellular antioxidant defence. [1][2][3] Observational studies have investigated coffee and caffeine intake in relation to type 2 diabetes, 4,5 depression 6 and insomnia 7 as well as various cancers, 8,9 but the directions of association have been inconsistent across diseases. 10 There are growing concerns regarding coffee consumption in relation to women's health.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the literature showed that an average higher caffeine consumption is associated with prolonged sleep latency (the time it takes to fall asleep), reduced sleep time, reduced sleep efficiency (percentage of time asleep of the total time in bed) and poorer sleep quality (Clark & Landolt, ). Moreover, caffeine consumption correlates positively with insomnia complaints (Chaudhary, Grandner, Jackson, & Chakravorty, ; Skarupke et al., ) and negatively with chronotype (being a “morning” versus an “evening” person) (Fabbian et al., ; Suh et al., ). Given the higher mortality rates and poorer health outcomes associated with sleep problems (Itani, Jike, Watanabe, & Kaneita, ; Tang, Fiecas, Afolalu, & Wolke, ), it is important to understand how caffeine consumption relates to different sleep behaviours.…”
Section: Introductionmentioning
confidence: 99%